LEGALITAS DAN PENGGOLONGAN ASET KRIPTO (STUDI PERBANDINGAN: INDONESIA DAN AMERIKA SERIKAT): Crypto Assets Legality and Classification (Comparative Studies: Indonesia and United States of America) - Sulaiman, Eric Joses; Wicaksana, Arif (AMICUS CURIAE, 2024)
Crypto Assets are digital assets that use blockchain-based cryptographic processes. Several countries already had regulations regarding Crypto Assets including Indonesia which classifies Crypto Assets as a commodity. Whereas in United States (US) Crypto Assets can be classifiedas a security. In this research discuss about legality,classification, and application of crypto assets in Indonesia and US. This research using normative research method with descriptive approach. Using secondary data and by documentation review, and the data analized by aqualitative. From this research can concluded there is difference clasificiation between Indonesia which classified Crypto Assets only as commodity and the US which not limit the classification of Crypto Assets, it can be commodity and also security. Examples of these Crypto Assets include XRP and AMP Tokens which are considered security by the Securities Exchange Commision. The suggestion is Indonesia should not directly classified all Crypto Assets as a commodity.